UJI POTENSI ANTI KANKER EKTRAK ETANOL BIJI KEBIUL (Caesalpinia bonduc (L) Roxb) DENGAN METODE BRINE SHRIMP LETHALITY TEST (BSLT) - Densi Selpia Sopianti; Aina Fathkil; Yesa Christine Sanuki (Oceana Biomedicina Journal, 2021)
Cancer becomes a global health problem which is estimated to continue to increase in number. The prevalence of cancer in Indonesia is 1.4% or around 347,792 people. Cancer treatment is currently carried out with chemotherapy, radiotherapy, and surgery. At present many active compounds from herbal plants are believed to be one of the alternatives used by the community as an anticancer, shown by several studies and the availability of active compounds from a single herbal plant isolated from plants as anticancer easily found by the community and have minimal side effects. One of the potential plants in Bengkulu is Kebiul (Caesalpiniabonduc (L.) Roxb) which, according to the Bengkulu community, is used for various diseases. The purpose of this study is that the researchers wanted to test the potential of the active compound of whistle seeds (Caesalpiniabonduc (L.) Roxb) with the Brine Shrimp Lethality Test method. The stages of this research were by making dried simplicia from whistle seeds then extracted with 96% ethanol and evaporated on a rotary evaporator until thick ethanol extract was obtained. The extract was tested using the BSLT Method, calculated the number of larval deaths and measured LD50. The results of the probit value equation analysis showed the LC50 value of the ethanol extract of whistle seeds was 11,1943μg/mL, this shows that the ethanol extract of the whistle seeds was very toxic which was indicated by LC50 values ​​<30 μg / mL.